Effects of GIS learning on high school students’ spatial-cognitive abilities. A case study of three secondary schools in Johannesburg. - Chipenda, Anne (My University, 2018)
The purpose of this study was to analyze the effects of GIS learning on high school students’ spatial abilities. 61 grade 11 learners, 31 doing Geography as a subject and 30 not doing geography, took part in the study. The learners, from three schools in Johannesburg, Parktown Boys High School, Parktown School for Girls and Marist Brothers Linmeyer, completed a pre and post spatial skills test during the first and third terms respectively, in 2017. Overall, the results showed a significant change from the pretest to the post tests of students who had done GIS learning. However, there were no significant differences between males and females. No significant differences were noted between students who spoke English as a first language and those who did not speak English as a first language. Different results obtained in the learners’ test results were examined; revealing that the GIS course had a positive effect on students’ spatial abilities, and that there was a positive relationship between the students’ spatial abilities and the outcome of their spatial skills tests. The students’ map drawing strategies did change for students who did GIS learning from landmark to route or survey, and not many changes were noticed for learners who did not do GIS learning. This showed that GIS learning had an effect on map drawing strategies
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements of the degree Master of Science (Geographic Information Systems and Remote Sensing), Johannesburg 2018
Keywords: Geographic information systems--South Africa; Geographic information systems--Study and teaching (Secondary)--South Africa; Spatial behavior--South Africa